The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1175/mwr-d-20-0373.1
|View full text |Cite
|
Sign up to set email alerts
|

How interactions between tropical depressions and western disturbances affect heavy precipitation in South Asia

Abstract: Interactions over South Asia between tropical depressions (TDs) and extratropical storms known as western disturbances (WDs) are known to cause extreme precipitation events, including those responsible for the 2013 floods over northern India. In this study, existing databases of WD and TD tracks are used to identify potential WD–TD interactions from 1979–2015; these are filtered according to proximity and intensity, leaving 59 cases which form the basis of this paper. Synoptic charts, vorticity budgets, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 92 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Interactions between tropical lows and extratropical troughs (Hong et al ., 2011; Vellore et al ., 2015; Houze et al ., 2017) are crucial for monsoonal precipitation in the WH. The intensity of the precipitation changes with the type of tropical and extratropical interactions (Hunt et al ., 2021). In M2 and M3, low‐level cyclonic circulations are strengthened by their interaction with subtropical trough.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between tropical lows and extratropical troughs (Hong et al ., 2011; Vellore et al ., 2015; Houze et al ., 2017) are crucial for monsoonal precipitation in the WH. The intensity of the precipitation changes with the type of tropical and extratropical interactions (Hunt et al ., 2021). In M2 and M3, low‐level cyclonic circulations are strengthened by their interaction with subtropical trough.…”
Section: Resultsmentioning
confidence: 99%
“…2). Such circulation will lead to the generation of ageostrophic vertical velocity, and depending on local factors (like orography and moisture), dramatic intensification can occur over the elevated topographies (Uccellini and Johnson, 1979; Vellore et al ., 2016; Hunt et al ., 2021), leading to extreme precipitation, as a result of a jet streak excitation as shown by Hunt et al . (2021).…”
Section: A Schematic Description Of the Life Cycle Of Extratropical I...mentioning
confidence: 88%
“…Vellore et al (2016) and Hunt et al (2018aHunt et al ( , 2018b, using cluster composite analysis, looked into several extratropical intrusions of western disturbances in a detailed manner and described the presence of monsoon low-pressure systems and western disturbance as a necessary condition for heavy events. Another recent study (Hunt et al, 2021) explained the extreme events in terms of the coexistence of monsoon low-pressure systems and western disturbances. They found that high-intensity precipitation occurs as a result of their interactions, but their analysis uses the perspective of Hanley et al (2001), which assumes the pre-existence of an intense cyclonic storm (with substantial azimuthal eddy flux transfer, EFCs which is a measure of local eddy forcing) co-located with the jet stream and that this storm interacts with the upper-level troughs when the eddy-induced azimuthal flux transfer measured by EFCs cross certain thresholds and provide necessary eddy forcing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khidher, S. A., & Pilesjö, P. 2015 [17] studied the North Atlantic Oscillation (NAO) Impact on the Climate of Iraq, they found that rainfall in Iraq rises during the NAO negative phase and falls during the positive phase. Hunt et al 2021 [18] looked at the devastating floods that hit northern India in 2013, they showed that the combination of the upper air trough and the powerful monsoon low-pressure system was principally responsible for the extreme rainfall events. Almazroui et al 2016 [19] studied the link between disturbances at 500 hPa geopotential height and rainfall in Saudi Arabia during the wet season.…”
Section: Introductionmentioning
confidence: 99%